2017
DOI: 10.1177/1746197917731353
|View full text |Cite
|
Sign up to set email alerts
|

What makes or breaks higher education community engagement in the South African rural school context: A multiple-partner perspective

Abstract: The purpose of this study is to inform global citizenship practice as a higher education (HE) agenda by comparing the retrospective experiences of a range of community engagement (CE) partners, and including often silent voices of non-researcher partners. HE-CE aims to contribute to social justice as it constructs and transfers new knowledge from the perspectives of a wide range of CE-partners. This qualitative secondary analysis study was framed theoretically by the transformative-emancipatory paradigm. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Scholars assert that to achieve true learning outcomes and fully understand a specific experience, researchers must understand students' motivation to participate in community engagement and must gather in-depth reflections and feedback for analysis (Bringle & Hatcher, 1999;Eyler & Giles, 1999). It appears researchers are more and more aware of the advantage of qualitative methods to incorporate data derived from participants' reflections and responses to open-ended questions (Duff et al, 2014;Machimana et al, 2018). In our sample, the qualitative studies captured the rich experiences of students and community partners involved in community engagement projects through participants' in-depth reflections.…”
Section: Research Methodologies Of Sampled Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Scholars assert that to achieve true learning outcomes and fully understand a specific experience, researchers must understand students' motivation to participate in community engagement and must gather in-depth reflections and feedback for analysis (Bringle & Hatcher, 1999;Eyler & Giles, 1999). It appears researchers are more and more aware of the advantage of qualitative methods to incorporate data derived from participants' reflections and responses to open-ended questions (Duff et al, 2014;Machimana et al, 2018). In our sample, the qualitative studies captured the rich experiences of students and community partners involved in community engagement projects through participants' in-depth reflections.…”
Section: Research Methodologies Of Sampled Articlesmentioning
confidence: 99%
“…One main purpose of service-learning is to serve the community and create change (Bringle & Hatcher, 1995); as such, projects impact individual students, institutions, communities, and even the whole social system (Bielefeldt & Lima, 2019). This change cannot be effected without a collaborative effort by community partners (Machimana et al, 2018). In community engagement projects, the community should be the driving force with a vision of partnering with student engineers (Bielefeldt & Lima, 2019).…”
Section: Community Partners' Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…One prominent theme in the literature regarding teams that cross academic and community settings is just how difficult they are to manage and support. An example is from a study by Machimana et al (2018), of the experiences of multiple higher community engagement partners on a decade-long partnership. They found that a common hindrance related to relationships and communication (i.e., unclear scope, inconsistent feedback and conflicting expectations).…”
Section: Contemporary Debates In Research Leadership and Collaborative Team Workingmentioning
confidence: 99%